A MODIFIED METHOD FOR CALCULATING STRESSES AND STRAINES OF NOTCH UNDER BIAXIAL LOADING CONDITION - LI YouSheng (Jixie qiangdu)
It has already been proved that the Neuber method overestimates the notch root stresses and strains and the equivalent strain energy density（ESED） method underestimates those,that is,the upper limit and lower limit can be obtained by the above two methods.On the basis of the analysis of results of notch root subjected to biaxial loading,a modified calculation method is proposed based on Neuber method in order to make up it’s shortage.Meanwhile,in the case of plastic stage,the effect of the material constants of elastic modulus,yield stress and poisson’s ratio on the stresses and strains should be considered and the results calculated by modified method should locate between those by Neuber method and the equivalent strain energy density method.Taking the LD5 notch sample as an example,the notch root stresses and strains are calculated.Finally the calculation results using modified method are validated with those by the finite element method.